Michał Czajkowski (Sadyk Pasha) and the policy of the Hôtel Lambert - Michalak, Paweł (Balcanica Posnaniensia. Acta et studia, 2011)
The article analyzes the activities of Michał Czajkowski, later known as Sadyk Pasha, in the context of the policy of the Hôtel Lambert camp led by Prince Adam Jerzy Czartoryski. The author presents the connections between religion, Polish émigré politics, and diplomatic activity conducted in the Ottoman Empire. The aim of the article is to demonstrate Czajkowski’s role in the activities of Hôtel Lambert and the significance of his conversion to Islam for the Polish political emigration. The author employs the historical method and an analysis of biographical sources, correspondence, and documents connected with émigré activities. The study demonstrates that Czajkowski was one of the most important political agents of Hôtel Lambert in the Ottoman Empire and played a significant role in organizing Polish political activity in the East. The author emphasizes that his conversion to Islam and adoption of the name Sadyk Pasha provoked numerous controversies among the Polish émigré community and was exploited in political disputes. The results of the analysis indicate that Czajkowski’s activities constituted an example of the close relationship between politics, religion, and national ideas within the milieu of the Great Emigration.